Amplification and Transposition in English Commands into Indonesian Translation with Reference to Harry Potter's Novel - Ni Putu Diah Darmayanti; Ida Bagus Putra Yadnya; I Nyoman Sedeng (Soshum: Jurnal Sosial dan Humaniora, 2019)
The research aimed at analyzing the equivalence between the source language and its translations based on the translation techniques proposed by Molina and Albir (2002). This research focused on the amplification and transposition techniques could be seen on the imperative sentences especially command. The research was conducted by using qualitative method. The data to support this research was taken from an Harry Potter’s novel entitled Harry Potter and The order of Phoenix” in English as source language (SL) and its translation into Indonesian novel as target language (TL). Library research and observation method were used in collecting of data. The technique of collecting data implemented by reading the novel and using note- taking. First step was taking the magazines then reading the novel to carefully understand how the source language (SL) in English were being translated into Indonesian translation in Target Language (TL). The second step was underlining the data of SL which were translated into TL then taking note those data that had been found into a paper or note book. The last step, the selected data were classified based on the objects investigated was techniques of translation. The instruments used were ball point and note book. The translator applied amplification and transposition to produce equivalences when transferring the meaning from the source language (SL) into target language (TL). Therefore, the overlapping translation could be minimized. Amplification had a role especially the addition of information. Some of data showed the phenomena when the detail information did not contain in the source language and the translator must be sensitive by putting the necessary information in target language. Meanwhile, transposition made a shift in translation as follows, structure shift, unit shift and class of shift. It occurred because of the different linguistics factor in SL into TL.